Adaptações de abelhas sem ferrão nativas da Caatinga (Melipona subnitida) para lidar com as temperaturas elevadas durante o forrageamento - Souza, Vinício Heidy da Silva Teixeira de (2017)
Owing to high environmental temperatures in combination with elevated solar radiation, the Brazilian SeasonallyDry Tropical Forest, the Caatinga, is a thermally challenging environment for bees, particularly during food collection outside of the nest. The aim of the present study was to investigate the adaptations of bees that allow these animals to survive the thermal conditions of this biome. As model species for our study, we used Melipona subnitida, a stingless bee species (Apidae, Meliponini), endemic from Caatinga. We analysed the following features: (1) the critical thermal maximum (CTmax) of the individuals (both young workers and foragers) as well as the best acclimation time for this kind of study (acclimation times tested: without acclimation, 20 min, 12 h, 48 h, 72 h); (2) The influence of ambient temperature in direct sunlight (Ta) on the thoracic temperature of foragers (Ttx); (3) the possible heat transfer from the thorax to the abdomen, assessed through the temperature difference between these two body parts associated with ambient temperature in both alive and dead individuals; and (4) the role of the thoracic hairs in heating and cooling rates of the bees. The results of the experiments demonstrated that (1) there was no significant difference concerning CTmax between young worker bees and foragers. After 48 hours of acclimation (acclimation time showing the highest CTmax and the lowest variation compared to the other acclimation times tested), the bees' average CTmax was 50.2°C ± 0.7. (2) The foragers' Ttx increased with increasing Ta. At Ta < 40°C, the bees' Ttx was higher than Ta; however, at Ta > 41°C, the forgers' Ttx remained below Ta. (3) There is a possible active heat transfer from the thorax (Ttx) to the abdomen (Tabd) given that, as Ta increased, the difference between Ttx and Tabd decreased in alive foragers. In dead individuals, in contrast, we did not observe this association with Ta. The difference between Ttx and Tabd was relatively constant over all studied Tas. (4) The thoracic hair slow down the heating of M. subnitida. Dead bees without thoracic hair had a higher heating rate than dead bees with their natural air cover. However, there was no difference between the two experimental groups concerning the cooling rates. The results of this study demonstrate that M. subnitida tolerates ambient temperatures that are higher than those found in their natural outside environment. In addition, foragers control their body temperature through active (heat transfer to the abdomen) and passive (thoracic hair) mechanisms, which enables the bees to forage at high environmental temperatures. Results like these of the present study provide important insights into the adaptations necessary to deal with increasing environmental temperatures, as predicted by global warming scenarios